Shallow crustal structure detection of the upper crust at Anqiu-Juxian Fault in the Tanlu fault zone - Huang, Qilong; Fan, Xiaoping; Fu, Wei; Zhang, Peng; Zheng, Tuo; Liu, Yunze; Zhang, Tiantian; Ren, Shiyu; Wang, Qinghui; Liu, Zhiwen; Qian, Ting (Frontiers in Physics, 2024)
Within the Tan-Lu Fault Zone, the largest active tectonic belt in eastern China, the Anqiu-Juxian Fault exhibits the most recent activity period, evident surface traces, and highest seismic hazard, making it a Holocene active fault. This study utilized the vertical component continuous data observed by 100 short-period temporary stations from August 1-21, 2023, and extracted 1,944 Rayleigh wave group velocity dispersion curves within the period of 0.2-4 s. Using the direct surface wave tomography method, we calculated a high-resolution 3-D shear-wave velocity structure at depths of 0.2-1.25 km within the study area. Our results are summarized as follows: (1) The development of faults F1, F2, and F5 in the Tan-Lu Fault Zone highly correlated with the shear-wave velocity anomalies at depths > 0.8 km. Specifically, fault F5 comprised two boundary faults, F5-1 and F5-2, which together controlled a Cenozoic depression covered by a thick, low-velocity sediment layer. (2) The complex velocity structure characteristics in the Suqian area revealed that the influence of faults on the sedimentary layers in the Suqian area was not expressed as an overall uplift or subsidence of the block but rather as differential subsidence. (3) Near Sankeshu, the F5 fault formed a small pull-apart basin. The latest activity in this pull-apart basin has shifted to the fault in the center of the basin, indicating that the pull-apart basin has entered the extinction stage.